POLA DEGRADASI DAN DEFORESTASI DI KESATUAN HIDROLOGIS GAMBUT (KHG) PROVINSI KALIMANTAN TENGAH TAHUN 2016 - 2017 (Degradation and Deforestation Pattern at the Peat Hydrological Unit (PMU) in Central Kalimantan Province at 2016-2017) - Yusuf Aguswan (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2019)
Deforestation rates on Kalimantan Island from 1990 to 2014 were recorded at 1.12% (± 0.36 million hectares) each year. Central Kalimantan has a forest decline rate of 1.36%. Land cover changes are important information in the management of forest areas. Changes in land cover are important information in the management of forest areas. This study was carried out throughout the Peat Hydrological Unit (PMU) in Central Kalimantan Province as many as 35 PMU with an area of 4,671,558 Ha. The method used is a quantitative method using ArcGIS 10.1 and Microsoft Excel software for dataanalysis. The data used are Land Cover Map Data in Central Kalimantan in 2016-2017, City/District Administration Area Map and Central Kalimantan Provincial Spatial Planning Map. The results obtained are Deforestation and Degradation in 2016 - 2017 occurred in 75% of the Peat Hydrological Unit Area in Central Kalimantan, in all spatial patterns in the PMU and in all district / city administrative areas